Pengaruh tingkat suku bunga dan kurs terhadap harga saham industri pertambangan batubara di Bursa Efek Indonesia periode 2014-2017 - Ahfazhi Ahfazhi; Fitriaty Fitriaty; Tona Aurora Lubis (Jurnal Dinamika Manajemen, 2019)
This study aims to examine the effect of the interest rate of Bank Indonesia and the exchange rate on the stock prices of the coal industry listed on the Indonesian securities exchange for 2014-2017period empirically. Data used in this study are multiple linear analyses and hypotheses. The independent variable is the interest rate of Bank Indonesia. The dependent variable is exchange rates at the coal mining industry stock price for 2014-2017. Data used in this study are secondary data obtained from the Indonesian stock exchange (IDX). The testing of the hypothesis in this study was tested using SPSS 23. The results showed that the interest rate of Indonesian banks had an effect of 18.75% and an effective exchange rate of44.22%, with a significant negative impact on the share price of the coal mining industry listed on the Indonesian stock exchange in 2014- 2017.